Review paperNew light on prions: putative role of co-operation of PrPc and Aβ proteins in cognition - Chrobak, Adrian Andrzej; Adamek, Dariusz (Folia Neuropathologica, 2014)
A seminal article of Takahashi et al. reporting concomitant accumulation of cellular prion protein (PrP c ) and β-amyloid (Aβ) in dystrophic neurites, within neuritic plaques raised an exciting issue that is important for our understanding of mechanisms of neurodegeneration. The mentioned authors interpreted their findings rather cautiously, however since the time of their publication, several reports representing different approaches and methods have seemed to indicate that both proteins appear to co-operate more intrinsically than it could have been imagined earlier. The goal of the review is to sum up the accruing research data with special attention to evidence pointing to the co-operative role of PrP c and Aβ in cognitive impairment.